Nursing education: The experience, attitudes, and impact of caring for dying patients by undergraduate argentinian nursing students - Mutto, Eduardo Mario (2010)
Background: There is extensive research documenting serious deficiencies in undergraduate nursing education related to end-of-life care. Many nurses and nursing students have difficulties in dealing with death and report feeling anxious and unprepared to be with patients who are dying. In Argentina, education on palliative care, death, and dying has not been made part of the undergraduate nursing curriculum. Methods: We performed a multicenter survey on undergraduate nursing education regarding the care of dying patients at eight schools of nursing in Buenos Aires, Argentina. We enrolled 680 students from first to fifth year. Results: Students acknowledged interacting directly with dying patients. Attitudes toward dying patients were highly positive. Students of the fifth year expressed a less satisfying relationship with their patients than those from the first year; considered it as a less gratifying occupation, and also showed a greater preference for avoiding emotional involvement with those patients. Discussion: Many of them described in short and very expressive phrases the emotional impact of their encounters with patients facing a life-threatening illness. Students perceived that this issue received more attention in humanistic rather than clinical subjects. Ninety-eight percent of students spontaneously demanded more training in end-of-life care. The interest and desire of undergraduate students to enhance their knowledge and experience in palliative care, demands more specific teaching contents. Conclusion: This suggests that in Argentina, improvements in undergraduate nursing training are urgently needed and would be well received by the students. It could be very useful to consider this topic as part of accreditation standards for nursing programs. © 2010 Mary Ann Liebert, Inc.